On the improvement of the remainder term for the multidimensional global theorems - Bikelis, A. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Бикялис. Об уточнении остаточного члена в многомерных глобальных теоремах A. Bikelis. Apie liekamojo nario pagerinimą daugiamatėse globalinėse teoremose